Architectural building materials : the new ladder type curriculum - Salvan, George Salinda (Quezon City, Philippines : JMC Press Inc., 1986)
This book discusses the properties of building materials, their application and articulation, system of construction, methods for specifying and their character in use. It is arranged in such a manner that the reader is provided with adequate knowledge on the characteristics uses of building materials. It also equips the reader with sufficient skill in the selection of and specification of building materials.
1. Concrete and concrete products -- 2. Ceramics and clay products -- 3. Building stones, gypsum and lime --- 4. Wood and wood products -- 5. Recycled water products building boards and papers -- 6. Bituminous material -- 7. Ferrous and non ferrous metals -- 8. Glass and glazing -- 9. Plastics and related products -- 10. Adhesives and sealants -- 11. Insulating materials -- 12. Building protection -- 13. Paints and coatings -- 14. Hardwares -- 15. Plumbing materials -- 16. Electrical materials -- 17. Flooring materials -- 18. Walling materials -- 19. Ceiling and acoustical materials -- 20. Roofing materials -- 21. Sample forms.
Keywords: BUILDING MATERIALS